Prevalence of Opioid-Related Problems and Their Association with Birth Outcomes Among Commercially Insured Pregnant Women - Kyungha KIM; Guodong LIU; Charleen HSUAN; Tammy E. CORR; Diana L. VELOTT; Megan S. WRIGHT; Sujeong PARK; Andrew W. DICK; Douglas L. LESLIE (Journal of Women's Health, 2026)
Objective: Although previous studies report increasing rates of maternal opioid use disorder documented at delivery, the extent to which pregnant women have a clinically recognized opioid-related problem in the year preceding delivery and the effects on pregnancy outcomes are unknown. Methods: We used the 2005–2018 MarketScan ® commercial claims database to identify women aged 13–49 years with a minimum of 12 months of continuous enrollment in the database. Among them, we further identified women with a delivery-related claim who were continuously enrolled for 12 months preceding delivery. Annual rates of opioid-related problems (ORPs), including misuse, dependence, and outdose, and of adverse birth outcomes (cesarean, preterm, and stillbirth delivery) by opioid-related problem status were compared over time. Results: We identified 2,995,032 births from 2,557,438 women who met inclusion criteria. Rates of ORPs in the year before delivery increased from 0.05% in 2006 to a high of 0.34% in 2016, a 7-fold increase, and then fell slightly to 0.29% in 2018. The multivariable regression with linear probability models showed that ORPs were associated with a higher likelihood of cesarean delivery (coefficient: 0.04; 95% confidence interval [95% CI]: 0.03–0.05) and preterm birth (0.05; 0.04–0.05). The effect was more moderate in association with stillbirth (0.00; 0.00–0.01). Conclusions: Rates of ORPs among pregnant women have increased over time and are associated with adverse birth outcomes. Future research should explore differences in birth outcomes by type of ORPs during pregnancy.